Effect of an online teaching module on midwives' knowledge, attitude and practice regarding intrapartum ultrasound: A quasi-experimental approach - Packet, Bram; Adela, Samešová; Jute, Richter (European journal of midwifery, 2024)
INTRODUCTION: Intrapartum ultrasound (IPUS) allows for a more reliable and reproducible assessment of fetal head station and position during labor. This study aimed to investigate how an online education module on IPUS impacts midwives' knowledge, attitudes, and practices (KAP) regarding this topic. METHODS: Midwives working in the labor ward of the University Hospital of Leuven (Belgium) were invited to participate in an educational program on IPUS in April 2023. A baseline KAP survey was completed upon enrolment, followed by an online education module on the intrapartum sonographic assessment of head station and position. Afterwards, a second KAP survey was completed. Score were compared using a two-sided Wilcoxon signed-rank test. A p<0.05 was considered significant. Statistical analyses were conducted using SPSS (version 29.0.2.0). RESULTS: A total of 45 midwives were eligible for inclusion and invited to participate. From these, 46.7% (21/45) agreed to take part. Attitudes towards IPUS were positive, as most perceived it as safe, time-efficient, and beneficial for medical-decision making. However, only two midwives (9.1%) sometimes used IPUS themselves during the second stage, whereas none used it during the first stage. A significant improvement in knowledge scores was recorded after the online education module for both the sections on fetal head station (median score 0/5 to 2.75/5, p=0.01) and position (median score 2.5/5 to 3.5/5, p=0.04). No significant differences were observed in the overall attitude scores, as they remained overall positive (4.5/5 to 5/5, p=0.18). CONCLUSIONS: Although having little experience with IPUS themselves, most participating midwives perceive it as an acceptable, time-efficient, and safe imaging modality. A short online education module resulted in a significant improvement in their knowledge of these topics. Further implementation research is needed to investigate how the uptake of IPUS amongst midwives can be improved, and how this can improve overall labor care.